Reliability and identification of aortic valve prolapse in the horse - Hallowell, Gayle D.; Bowen, Mark (BioMed Central, 2013)
Background The objectives were to determine and assess the reliability of criteria for identification of aortic valve prolapse (AVP) using echocardiography in the horse.